A Critical Review of Timber as a Structural Material (OCEM Journal of Management, Technology & Social Sciences, 2024)
The structure refers to the component of the building that maintains its stability. The beam, column, slab, and foundation are the major integral units of the structure. The major challenge while designing the structure for a building is to select materials for its units. Generally, reinforced cement concrete (RCC) is used worldwide in the current context. The search for the perfect material to replace RCC has been ongoing for decades. Timber can be the perfect material everyone has been searching for. It is made of wood, which is harvested from trees. This paper focuses on the process of installation and mechanical properties that make timber suitable for construction. Timber has ideal characteristics and mechanical properties that make it fit for the structure. Several mechanical properties have been tested in the lab, making timber a suitable replacement for existing RCC.The timber has a compressive strength of 500 Kg/cm2 to 700 Kg/cm2, which makes it mechanically acceptable to use as a structural material. It also has other mechanical properties in acceptable ranges. The tensile strength of timber is 500 Kg/cm2 to 2000 Kg/cm2. It also has a favourable density of 300Kg/M3 to 900Kg/M3. Several problems occur with timber, too, which makes it questionable. But still, timber holds good credit. Major problems with timber, for example,  low fire resistance, difficulty installing, and decay after contact with moisture, can be solved by applying the respective remedies. Overall, timber can be one of the best replacements for RCC in terms of suitability.